Solution Thermodynamics of Lysine Clonixinate in Some Ethanol+ Water Mixtures (2023)
The solubility of lysine clonixinate (LysClon) in several ethanol + water mixtures was determined at 293.15 to 313.15 K. The thermodynamic functions, Gibbs energy, enthalpy, and entropy of solution and of mixing were obtained from these solubility data by